An Examination of COVID‐19 Mortality in High‐Minority Nursing Homes. (15th September 2021) - Weech‐Maldonado, Robert; Lord, Justin; Davlyatov, Ganisher; Ghiasi, Akbar; Orewa, Gregory
Abstract : Research Objective: Racial/ethnic disparities in healthcare have been highlighted by the recent COVID‐19 pandemic. Using the Centers for Medicare and Medicaid Services' Nursing Home COVID‐19 Public File, we examined the relationship between nursing home racial/ethnic mix and COVID‐19 resident mortality. Additionally, we examined the effects of resident characteristics, market resource availability, and organizational characteristics as it relates to nursing home racial/ethnic disparities in COVID‐19 mortality. Study Design: Multivariate regressions were used to model the relationship between COVID‐19 deaths and the proportion of racial/ethnic minority residents (Black and Hispanic residents). Given the over‐dispersion of the count dependent variable (number of COVID‐19 deaths), negative binomial regressions were used. We used four nested sequential models to examine the separate contributions of facility‐level resident characteristics, resource availability, and other organizational characteristics to racial/ethnic disparities in COVID‐19 deaths. In addition, we controlled for size and interstate differences using state fixed effects. Population Studied: The study sample consisted of all US nursing homes included in the CMS Nursing Home COVID‐19 Public File, or 15, 382 nursing homes, which mirrors the national census of facilities. Principal Findings: As of October 25, 2020, high minority nursing homes reported 6.5 COVID‐19 deaths as compared to 2.6 deaths for nursing homes that had no racial/ethnic minorities. After controlling for interstate differences, facility‐level resident characteristics, resource availability, and organizational characteristics, high‐minority nursing homes had 61% more COVID‐19 deaths (Incidence Rate Ratio [IRR] = 1.61; p < 0.001) as compared to nursing facilities with no minorities. Conclusions: From a policy perspective, nursing homes, that serve primarily minority populations, may need additional resources, such as, funding for staffing and personal protective equipment in the face of the pandemic. The COVID‐19 pandemic has sharpened the focus on healthcare disparities and societal inequalities in the delivery of long‐term care. Implications for Policy or Practice: This study shows the disparate effect that COVID‐19 has had on nursing home mortality based on resident racial/ethnic mix. Even after controlling for interstate differences, facility‐level resident characteristics, resource availability, and organizational characteristics, high‐minority nursing homes had almost three times the probability of having COVID‐19 deaths compared to those with no minorities. These findings highlight the existing and systemic health disparities in nursing homes and the tangible impact it has on racial/ethnic minorities. Death due to COVID‐19 is greater risk for racial/ethnic minorities in nursing homes relative to White residents. Nursing homes that serve larger minority populations may need additional resources to combat this crisis.